Ring chromosome 8 and trisomy 8 in a patient with acute myeloid leukemia - Kar, Bibhas (Springer-Verlag, 2009)
We describe a child with Acute Myeloid Leukemia (AML M7) with trisomy 8 and ring chromosome 8. Ring chromosome 8 associated with AML is uncommon and is reported to have a poor outcome. The combination of trisomy 8 and ring chromosome 8 has not been previously reported. This 15-month-old girl had presented with a history of fever, weight loss of 1 kg, gum bleeds and pallor. Clinical examinations revealed no nodes or organomegaly. Investigations revealed pancytopenia and elevated serum LDH. Bone marrow aspirate confirmed the presence of myeloid blasts positive only for CD 41 and CD 61 on flow cytometry. Chromosomal analysis from the bone marrow showed 46, XX [13]/ 47, XX, +8[2]/ 47, XX, +r (8) [5]. The child was treated as per UK MRC AML protocol (ADE 10+3+5). Bone marrow on day 21 post-induction was in morphological remission. Repeat karyotyping revealed 46,XX suggesting that the patient was in cytogenetic remission. Cytogenetic sub grouping in AML patients provides guidelines for the choice of optimal treatment strategy. There was no HLA matched family donor and hence an unrelated donor search was commenced as she was in the group with unfavourable cytogenetics. She developed acute myelofibrosis soon after the second cycle of chemotherapy with swinging fever and rapidly enlarging spleen. The marrow showed 11% blasts with intense fibrosis. She went through a stormy period during conditioning for unrelated stem cell transplantation. She passed away on day 11 post transplantation of veno-occlusive disease of liver and multiorgan failure. This case illustrates the poor outcome in paediatric AML with trisomy and ring chromosome 8.